49‐3: High Power Laser Phosphor Light Source Using a Scanning Mirror for Projectors. Issue 1 (28th June 2021) - Li, Kenneth; Chang, Y.P.; Chen, Andy; Wang, Lion; Tsai, Stark
Abstract : With the advancement of blue laser developments at low cost, laser diodes and laser diode arrays are getting popular in various light system from low power to very high power. This paper presents a stationary phosphor system in which the phosphor plate is not in motion and can be attached to heat sinks for efficient removal of heat for high power operations, which cannot be achieve easily when the phosphor material is coated onto a rotating wheel. The highest effective power density, limited by the available laser source and the current heat sinking, of over 301 W per sq. mm has been achieved and is expected to increase in the near future with higher power laser sources and improved heat sinking.